PENGARUH KUALITAS PRODUK, HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN HAND SANITIZER NATURE LEAF PADA REMAJA DI SURAKARTA - Nia Rahma Astuti (Program Studi Manajemen Fakultas Ekonomi UST, 2021)
This article was created to prove that the decision to purchase Hand Sanitizer Nature Leaf in Remaja Surakarta is influenced by product quality, price and brand. Multiple Linear Regression Analysis was chosen as the research method of course using the 2016 version of SPSS. The result obtained is the purchase decision is influenced by the quality of the product, for variable prices showed a significant impact & For variable Brands showed a significant where the purchase decision was influenced by the Brand